Factors governing seawater carbonate dynamics in a macroalgal habitat - Kim, Ja-Myung; Lee, Kitack; Han, In-Seong; Kim, Miok; Kim, Ju-Hyoung; Kim, Tae-Hoon; Kim, HyunKyum; Jeon, Byung Hee; Shin, Kyoungsoon (Frontiers in Marine Science, 2022)
Photosynthetic organisms shift the dynamics of surface pCO2 driven by the sea surface temperature change (thermodynamic driver) by assimilating C from seawater. Here we measured net C uptake in a macroalgal habitat of coastal Korea for two years (2019-2020) and found that the macroalgal habitat contributed 5.8 g C m-2 month-1 of the net C uptake during the growing period (the cooling period, September-May). This massive C uptake changed the thermodynamics-driven seasonal dynamics such that the air-sea equilibrium of pCO2 was pushed into disequilibrium. The surface pCO2 dynamics during the cooling period was mostly influenced by the seasonal decrease in temperature and the proliferation of macroalgae, while the dynamics during the warming period (the stagnant period, June-August) closely followed that predicted based solely on the change in sea surface temperature only (thermodynamic driver). In contrast to the phytoplankton-dominated offshore waters (where phytoplankton populations are large in spring and summer), the impact of coastal water macroalgae on surface pCO2 dynamics was most pronounced during the cooling period, when the magnitude of pCO2 change was as much as twice that resulting from temperature change. Our study shows that the distinctive features of the macroalgal habitat—in particular the seasonal temperature extremes ( 18oC difference), the active macroalgal metabolism, and anthropogenic nutrient inputs—collectively influenced the seasonal decoupling of seawater and air pCO2 dynamics.